Isolation of a fragment of tau derived from the core of the paired helical filament of Alzheimer disease. - Wischik, C M (1988)
A substantially enriched preparation of Alzheimer paired helical filaments (PHFs) has been used as a starting point for biochemical studies. Pronase treatment, which strips off adhering proteins, leaves a resistant core that is structurally intact. This has been used to raise a monoclonal antibody that decorates the filament core. The antibody has been used to follow the extraction of two peptide fragments (9.5 and 12 kDa) by immunoblotting. The link between the PHF as a morphological entity and these peptides has been established independently by photoaffinity labeling with a chemical ligand to the PHF core. Sequence analysis of these peptides was used to design oligonucleotide probes for cloning a cognate cDNA, which leads to its identification as human microtubule-associated tau protein. The sequencing of the 9.5- and 12-kDa peptides shows they are derived from a conserved region of tau containing three repeating segments. Since these fragments have been copurified with the Pronase-resistant core and are only released by subsequent steps, the corresponding part of the tau molecule must be tightly bound in the PHF core.